ERGONOMIC AWARENESS AND EMPLOYEE PERFORMANCE AMONG STAFF IN CONSTRUCTION INDUSTRY AT JOHOR BAHRU - Ismail, Fadillah; Chan, Shiau Wei; Mohd Rosli, Nur Amalina; Mohd Yusof, Farahwahidah (Jurnal 'Ulwan, 2025)
Ergonomic is the science and practices of designing jobs and enhancing the fit between the employees who perform the work and the physical demands of the work environment. Moreover, the application of ergonomics will be able to enhance employee performance. Therefore, this research was carried out to identify the relationship between ergonomic awareness and employee performance among staff in the construction industry in Johor Bahru. The objective of this study was to identify the level of ergonomic awareness in the construction industry and the level of employee performance. The entire population of office employees in the construction industry in Johor Bahru, with a total of 357 persons, and only 123 office workers, had been chosen to be the respondents for this research. Descriptive statistics and Pearson correlation analyzed the data obtained by using the Statistical Package for the Social Science 23.0 (SPSS version 23.0). The result of the study shows the level of ergonomic awareness in the construction industry is moderate, and also the level of employee performance. In addition, there is a positive relationship between ergonomic awareness and employee performance among office employees in the construction industry and a high correlation between ergonomic awareness and employee performance.